2018
DOI: 10.1002/tsm2.44
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic analysis of the ankle joint on the side-hop test in subjects with ankle sprains

Abstract: The side-hop test (SHT) is useful functional performance test for ankle sprain.However, few research exists to investigate the relationship between the SHT and functional deficit in ankle. The objective of this study was to establish SHT as an evaluation criterion of functional deficits in ankle sprain. Twenty-seven subjects with a history of ankle sprain participated. The time taken to perform SHT in the uninjured and injured limbs was measured. The angular displacements of the ankle joint were measured using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
1
1
Order By: Relevance
“…Our finding that only the BFR+R led to a significant improvement in timed performance during the SHT supports our hypothesis. This finding is consistent with that of a previous study by Yoshida et al (2018) who reported long performance time (worse) of the involved limb during the SHT and a delayed muscle activity of fibularis longus, tibialis anterior, and gastrocnemius muscles in patients with ankle sprain. The explanation for such improvement is unclear, but it may be related to greater strength gains in the BFR+R versus the R program.…”
Section: Discussionsupporting
confidence: 93%
“…Our finding that only the BFR+R led to a significant improvement in timed performance during the SHT supports our hypothesis. This finding is consistent with that of a previous study by Yoshida et al (2018) who reported long performance time (worse) of the involved limb during the SHT and a delayed muscle activity of fibularis longus, tibialis anterior, and gastrocnemius muscles in patients with ankle sprain. The explanation for such improvement is unclear, but it may be related to greater strength gains in the BFR+R versus the R program.…”
Section: Discussionsupporting
confidence: 93%
“…The FADI was examined as a measure of foot and ankle functional restriction in CAI because persons with CAI typically complain about their ankles giving way during functional tasks. [ 26 ] Our finding that BFR + R and R resulted in a significant improvement in FADI outcome measures contradicts the findings of Yoshida et al, [ 27 ] who found that patients with ankle sprain had a prolonged performance time of the affected leg and delayed muscle activation of the fibularis longus, tibialis anterior, and gastrocnemius muscles. In our study, the cause of this gain could be linked to stronger ankle plantar flexor and evertor muscles in the BFR + R and R than the BFR alone.…”
Section: Discussioncontrasting
confidence: 83%
“…Although the SHT is one of the most widely used functional test to assess ankle stability and has undergone the most research (Ortiz et al, 2005) in relation to lower limb functional performance (Gustavsson et al, 2006), there is still a lack of knowledge addressing the issue of the measurement characteristics of SHT. Stopwatches are up to date the most commonly used to measure the SHT performance (Docherty et al, 2005;Ortiz et al, 2005;Ortiz et al, 2011;Yoshida et al, 2011;Yoshida et al, 2018;Kamonseki et al, 2018), the measurement characteristics of mentioned test could be questionable. Alternative to stopwatch could be the contact matt which allows not only more reliable measures (Garcia-Lopez et al, 2005) but also the measurement of duration of every single phase of SHT, i.e., medial and lateral contact and "flight" times.…”
Section: Introductionmentioning
confidence: 99%